Angle- and strain-independent coloured free-standing films incorporating non-spherical colloidal photonic crystals1. Issue 8 (28th February 2015) - Yeo, Seon Ju; Tu, Fuquan; Kim, Seung-hyun; Yi, Gi-Ra; Yoo, Pil J.; Lee, Daeyeon
<x xml:space="preserve">Abstract</x> A method to fabricate large-area free-standing films of colloidal photonic crystals which exhibit angle- and strain-independent structural colour is presented.